Antibacterial Efficacy of Ethyl Acetate Fraction of Siwak (Salvadora persica)-NaOCl Combination as a Root Canal Irrigant against Enterococcus faecalis: An In Vitro Study - Kusuma, Andina Rizkia Putri; Ratih, Diatri Nari; Irnawati, Dyah -; Nuryono, Nuryono - (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Root canal irrigant is a very important factor in supporting the success of root canal treatment. The currently recommended combination of sodium hypochlorite (NaOCl), ethylenediamintetraacetic acid (EDTA), and chlorhexidine has many drawbacks including toxicity to periapical tissues, bad taste, negative interactions between ingredients, and extended application time. Siwak (Salvadora persica) stem extract has been widely studied in its use as a dental material, including as a root canal irrigant. This study aims to formulate the ethyl acetate fraction of siwak with low concentration NaOCl, and test its antibacterial potential against E. faecalis. This research used 9 groups, namely the ethyl acetate fraction (FEA) of siwak ethanol extract with the concentrations of 1.25 mg/ml, 2.5 mg/ml, 5 mg/ml, a combination of FEA siwak 1.25 mg/ml + NaOCl 1.25%, FEA siwak 2.5 mg/ml + NaOCl 1.25%, FEA siwak 5 mg/ml + NaOCl 1.25%, NaOCl 1,25%, saline, and chlorhexidine. Based on the number of colony counts, the most significant inhibition was seen in the combination group of FEA siwak 5 mg/ml + NaOCl 1.25%. Data analysis was carried out using the One Way ANOVA test with a significance value of 0.00 (p <0.05) followed by the Post Hoc LSD test with a significance value of 0.130 (p>0.05) in the comparison between the combination group of FEA siwak 5 mg/ml + NaOCl 1.25% with chlorhexidine. The combination of FEA siwak 5 mg/ml + NaOCl 1.25% has the same effectiveness as chlorhexidine 2% in inhibiting E. faecalis bacteria, and potential as a root canal irrigant.